The Legal System of the Social Health Insurance in Egypt and its Impact on Iraq - Reda, Ons; Rasheed, Saba (Journal of Legal Sciences, 2023)
Iraq issued the social Health Insurance Law No. 2 in 2020, thus taking its first step to introduce the universal health coverage. When the previous law was enacted, it was inspired by a number of countries, including the Arab Republic of Egypt, which began implementing the health insurance system since 2018, calling it universal health insurance and issued its law No. 2 of 2018, which was entitled as "The universal Health Insurance Law of the Arab Republic of Egypt". A national project at the all state level, such as the health insurance project, needs a set of equipment, both in terms of preparing the infrastructure or in terms of cooperation with health institutions in the public and private sectors, and both in terms of automating and mechanizing the health insurance system, as well as equipping the body that manages the system, in addition to the necessity of Determining the financial sources that will feed the system and contribute to its sustainability. Therefore, we decided to benefit from the Egyptian experience in this field, as it was the preceded before Iraq, and the fact that the introduction of the social health insurance system has brought about a remarkable change and development in the field of health care in Egypt, despite the challenges facing the application of the system in it.